True Biographies of Nations? The Cultural Journeys of Dictionaries of National Biography - Fox, Karen (ANU Press, 2019)
Dictionaries of national biography are a long-established and significant genre of biographical and historical writing, existing in many forms across the globe. This book brings together practitioners from around the English‑speaking world to reflect on national biographical dictionary projects' recent cultural journeys, and the challenges presented to them by such developments as the transition to a digital environment, a new alertness to the need to represent diversity, and the rise of transnationalism. Exploring their paths forward, the chapters of this book collectively make a powerful argument for the continued value and importance of large‑scale collaborative biographical dictionary research.